Consumer behaviour of internet users in Singapore and Malaysia. - Lee, Chin Hin. (2008)
This research aims to study the consumer behavior of Internet users in Singapore and Malaysia during 1998-2000. It is primarily concerned with understanding how such factors as demographics, social networks and psychological aspects relate with the consumer behavior on the Internet. This study endeavors to develop theoretical and methodological frameworks by consolidating a number of existing theories and concepts from consumer research and communication studies. In particular, the Hoyer & Maclnnis's Conceptual Model of Consumer Behavior.